Professional Zakat Distribution Strategyat YBM PLN UID South Central Kalimantan - Zulfariannur; Muhammad Zainal Arifin; Zulkifli; Muhammad Noor Sayuti (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2026)
This study aims to examine the professional zakat distribution strategy implemented by the Baitul Maal Foundation of the State Electricity Company Distribution Unit (YBM PLN UID) in South and Central Kalimantan, with the goal of effectively distributing professional zakat in both provinces. This study employs a descriptive qualitative method using a case study approach, conducted from June to July 2025. Primary data were obtained through in-depth interviews with foundation administrators, zakat officers (amil), and zakat recipients (mustahik), as well as direct observation of the professional zakat distribution process. Secondary data were collected from internal foundation documents, annual reports, and relevant literature. We carried out thematic data analysis by reducing the data, displaying it, and drawing conclusions in a structured way. The results of the study indicate that the professional zakat distribution strategy of YBM PLN UID South and Central Kalimantan involves both direct and indirect distribution patterns with consumptive and productive approaches. The distribution process includes structured planning, data collection, distribution, and evaluation. The segmentation of mustahik is based on strict socio-economic criteria to ensure targeted assistance. Moreover, challenges associated with the application of Good Amil Governance principles are pinpointed by this research, while suggestions are offered to improve the efficacy of strategies for distributing professional zakat moving forward